D. 7,4,29 A IN IURE CESSIO USUSFRUCTUS DOMINO PROPRIETATIS - Służewska, Zuzanna (Zeszyty Prawnicze, 2017)
D. 7,4,29 and in iure cessio ususfructus domino proprietatis Summary The problem discussed in my article concerns the non-transferability of the usufruct right and a remedy for this non-transferibility that consisted in the possibility of selling or hiring the usufruct to third parties. The usufruct as being servitus personarum was strictly attached to the person of usufructuary and could not be validly transferred to third parties. In iure cessio ususfructus could be done exclusively toward the bare owner, inwhich case the right of usufruct was extinguished through consolidationwith the property right, but not in favor of the third parties (Gai. 2,30; D. 23,3,66; I. 2,4,3). Nevertheless usufructuary could dispose his right on the contractual level and grant the enjoyment of the usufruct to otherpersons on the basis of the contract of sale or hire or donation orprecarium (such a contract could be validly stipulated until the death ofusufructuary in which moment the usufruct right was always extinguishedthrough the consolidation with the property right). In all cases mentioned above the usufructuary retained his right which was not extinguished by non usus since it was possible to recognize a purchaser, a hirer, a donee and any other person authorized by usufructuary as exercising this right in the name of the usufructuary. Even though that person who was enjoying the right of usufruct subsequently sold or hired it to another person the right of usufruct did not extinguish because any other person to whom a person authorized by usufructuary granted the enjoyment of the usufruct was still exercising this right in the name of the actual usufructuary. The particular case of such contract made by the usufructuary was analyzed by Pomponius in D. 7,4,29pr.-1: the owner of the land has rented it from the usufructuary and then sold it without reserving the right of usufruct. In this case, even though the vendor pays the rent to the usufructuary (the bare owner is liable to the usufructuary for quanti interfuit) the righ of usufruct is lost because the purchaser would have held the land in his own name, not that of the usufructuary. Similarly in case in which the bare owner purchased the usufruct from the usufructuary and then sold it to another person, the usufructuary lost his right since the buyer could not be deemed recognized as exercising this right in the name of the usufructuary. We can thus note that the effects of selling or hiring the usufruct to the bare owner were in fact very close to the effect of in iure cessio ususfructus domino proprietatis - the usufructuary lost his right and the bare owner could dispose his property without any limitations. The formal difference concerned the moment in which the right of usufruct was extinguished. In case of in iure cessio ususfructus domino proprietatis it was extinguished through the consolidation with the property in the moment in which the usufructuary ceased his right toward the bare owner. In case of selling or hiring this right to the bare owner, theoretically the usufructuary retained his usufruct until this owner dispose his property to third person in his own name (without reserving the existing usufruct), but in fact since the moment he sold or hired his right to the owner he lost the possibility of exercising his right and the owner could dispose his property as if it was not limited by any existing servitude. Such a solution did not cause any damage to the usufructuary (in both cases he was paid by the owner an economical value of his right) and at the same time it became possible to avoid the maintaining of limitations of one’s property and to protect the person who bought the thing from the owner without being informed ofthe existence of any servitude.